CEO compensation, firm size and firm performance: Evidence from Finnish panel data - Mikko Mäkinen (The Research Institute of the Finnish Economy (ETLA), 2007)
This paper examines how CEO pay is related to firm size and to firm performance in Finland by using new individual-level compensation data in 1996-2002. We find robust evidence that CEO average compensation has increased substantially between 1996 and 2002. For example, the ratio between CEO and industrial worker mean total compensation was 7 in 1996, peaked at 24 in 2000, and thereafter dropped to 13 in 2002. We argue that the change in CEO compensation, and especially in total compensation, is highly related to changes in stock market measures of firm performance. Our shareholder wealth measure suggests that the salary and bonus change in CEO wealth is exteuro6.84 per exteuro1,000 change in shareholder wealth. Respectively, the total compensation change is exteuro21.85 per exteuro1,000 change in shareholder wealth. We find no evidence on the contemporaneous link between a change in CEO compensation and change in ROA% (Return on Assets). However, one-year lagged accounting and stock market based firm performance measures are associated with the change in CEO total compensation. In line with previous studies, our findings suggest that pay-for-firm size elasticity is close to 0.3. We also find interesting corporate governance findings. First, the share of foreign ownership is positively
Keywords: J33; M52; L25; 330; Führungskräfte; Gehalt; Erfolgsbeteiligung; Aktienoption; Eigentümerstruktur; Finnland